Selective Loss of Brain-Derived Neurotrophic Factor Exacerbates Brain Injury by Enhancing Neuroinflammation in Experimental Streptococcus pneumoniae Meningitis - Zhao, Shengnan; Zhang, Zhijie; Xu, Danfeng; Wang, Yanfei; Li, Ling (Frontiers in Immunology, 2020)
Streptococcus pneumoniae meningitis is a life-threatening bacterial infection of the central nervous system (CNS), and its unfavorable prognosis usually results from an intense inflammatory response. Recent studies have shown that brain-derived neurotrophic factor (BDNF) mediates anti-inflammatory and neuroprotective effects in CNS diseases; however, the distinct contribution of BDNF to pneumococcal meningitis (PM) remains unknown. In this study, we sought to investigate the effects of endogenous BDNF on the inflammatory response and brain damage in experimental PM. We used Camk2a-CreERT2 mice to delete Bdnf from the cerebral cortex and hippocampus, and meningitis was induced by intracisternal infection with S. pneumoniae. Clinical parameters were assessed during acute meningitis. At 24 h postinfection, histopathology, neutrophil granulocytes infiltration and microglia/macrophage proliferation of brain tissues were evaluated. Additionally, cortical damage and hippocampal apoptosis were assessed using Nissl staining and terminal deoxynucleotidyl transferase dUTP-nick-end labeling (TUNEL), respectively. Pro-inflammatory cytokine levels were determined using real-time polymerase chain reaction (RT-PCR). Key molecules associated with the related signaling pathways were analyzed by RT-PCR and western blot. To investigate the role of microglia/macrophage in infected BDNF conditional knockout mice, GW2580 was used for microglia/macrophage depletion. Here, we, for the first time, found that BDNF conditional knockouts exhibited more profound clinical impairment, pathological severity, and neuron injury and enhanced microglia/macrophage proliferation than were observed in their littermate controls. Furthermore, the BDNF conditional knockouts showed an obviously increase in the expression of pro-inflammatory factors (Tnf-α, Il-1β and Il-6). Mechanistically, loss of BDNF activated TLR2- and NOD2-mediated downstream nuclear factor kappa B (NF-κB) p65 and p38 mitogen-activated protein kinase (MAPK) pathways associated with S. pneumoniae infection. Furthermore, targeted depletion of microglia/macrophage population decreased the resistance of mice to PM with diminishing neuroinflammation in BDNF conditional knockouts. Our findings suggest that loss of BDNF may enhance the inflammatory response and contribute to brain injury during PM at least partially by modulating TLR2- and NOD2-mediated signaling pathways, thereby providing a potential therapeutic target for future interventions in bacterial meningitis pathologies.